The impact of intranet on managers and their work : an empirical study in the Malaysian port industry / Norzaidi Mohd Daud … [et al.] - Mohd Daud, Norzaidi; Chong, Siong Choy; Mohamed, Intan Salwani; Raman, Murali (Faculty of Business and Management ; UiTM Press, 2009)
This paper examines the impact of Intranet usage on managers' performance in the port industry in Malaysia. Using the task-technology fit model, it investigates how certainfactors (e.g. task requirements, Intranet functionalities, task-technology fit, and Intranet usage) affect the job performance of port managers. The mean test results suggest that the majority of managers believed that Intranet could improve their job performance. The results of structural equation modelling (SEM) indicate that task requirements and Intranet functionalities significantly justified their variance on task-technology fit. Task technology fit, on the other hand, significantly predicts Intranet usage and both significantly explained the variance on manager's job performance. Suggestions are made on how the port industry could improve their Intranet adoption.